2020
DOI: 10.1186/s10194-020-01200-8
|View full text |Cite
|
Sign up to set email alerts
|

Individual pain sensitivity is associated with resting-state cortical activities in healthy individuals but not in patients with migraine: a magnetoencephalography study

Abstract: Background Pain sensitivity may determine the risk, severity, prognosis, and efficacy of treatment of clinical pain. Magnetic resonance imaging studies have linked thermal pain sensitivity to changes in brain structure. However, the neural correlates of mechanical pain sensitivity remain to be clarified through investigation of direct neural activities on the resting-state cortical oscillation and synchrony. Methods We recorded the resting-state ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 68 publications
2
15
0
Order By: Relevance
“…In previous studies, during capsaicin-heat pain stimulation, peak alpha frequency over the sensorimotor region was inversely correlated with individual pain intensity [11,13]. In our recent study, we further confirmed that pain sensitivity is associated with the spontaneous regional oscillatory activities and intrinsic functional network [14]. Taken together, these findings suggest that cortical activation and functional network may reflect individual pain sensitivity and cause individual differences in pain perception.…”
Section: Introductionsupporting
confidence: 85%
See 3 more Smart Citations
“…In previous studies, during capsaicin-heat pain stimulation, peak alpha frequency over the sensorimotor region was inversely correlated with individual pain intensity [11,13]. In our recent study, we further confirmed that pain sensitivity is associated with the spontaneous regional oscillatory activities and intrinsic functional network [14]. Taken together, these findings suggest that cortical activation and functional network may reflect individual pain sensitivity and cause individual differences in pain perception.…”
Section: Introductionsupporting
confidence: 85%
“…As resting-state brain activities were associated with individual pain sensitivity in our recent study [14], spontaneous cortical oscillations and intrinsic functional networks might be pivotal mechanisms in the regulation of pain processes. Therefore, this study combined multimodal (neurophysiology and psychometrics) signatures, which might better represent pain complexity, and built a multivariate machine-learning model, which learns from the features of psychometric scores (from demography and questionnaires), spontaneous brain oscillatory powers (from within-electrode EEG analysis), and resting-state functional connectivity (FC, from between-electrode EEG analysis), to noticeably classify the training dataset and predict the testing dataset on individual heat pain sensitivity derived from the heat pain threshold (HPT).…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…A new era for migraine treatment was opened with the use of large molecules acting on CGRP, the main mediator of sterile inflammation. The CGRP-mAbs act at the peripheral level, with an improbable and weak effect on the CNS [ 82 ], which would reduce their long term efficacy on the complex migraine brain dysfunction. However, a very recent study reported that a single dose 70 mg of enerumab caused a relevant change of functional connectivity from the hypothalamus to the insula, temporal lobe, hippocampus and trigeminal nuclei.…”
Section: Perspectives (In View Of Peripheral Cgrp Approach)mentioning
confidence: 99%